Improving Bounce Pass Skills in Basketball Games Using the Problem Based Learning Method - Madyana Hari, Dini Marta; Luthfia, Wulandari; Fahmi, Erwinsyah Riski; Andik, Cahyono; Hari, Pamungkas (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
This research uses a problem-based learning approach with a learning sequence of observation, evaluation, and progress monitoring to measure the improvement of individual bounce pass skills. During the learning process, learners are invited to identify problems or difficulties they face in performing the bounce pass. Collaborate in finding solutions to overcome these problems. Conduct learning and simulation of game situations that allow the application of the